Illegal logging, collusive corruption and fragmented governments in Kalimantan, Indonesia - Smith, J.; Obidzinski, K.; Subarudi, S.; Suramenggala, I. (Earthscan, 2007)
The paper distinguishes between collusive and non-collusive corruption in the forestry sector and analyses their interaction with the political/institutional environment. While non-collusive corruption increases costs for the private sector, collusive corruption reduces costs for the bribee, therefore it is more persistent. Data from confidential interviews in Indonesia show that illegal logging, supported by collusive corruption, became widespread after the fall of President Suharto. While economic liberalisation and competition among government officials may lower non-collusive corruption, they exacerbate collusive corruption. During political transitions, countries are particularly vulnerable to collusive corruption because governments are often weak and fragmented, with underdeveloped institutions. Sustained wider reform and institutional strengthening to speed up the transition to a true democracy is needed to fight collusive corruption. For Indonesia greater accountability of government, legal and judicial reform and encouragement of public oversight could be useful corner stones for combating illegal logging and corruption.